POLA PENGEMBANGAN PONPES NW PASCA WAFATNYA TGH. M. ZAINUDDIN ABDUL MAJID - Muhtar, Fathurrahman (JURNAL PENELITIAN KEISLAMAN, 2013)
This research is to answer fundamental issues in conflict management institutions of Islamic education in Pondok Pesantren Nahd}atul Wat}an namely: first,. source of authority and authority in managing the praxis of Islamic educational institutions in boarding Nahdlatul Wathan East Lombok NTB causes of conflict and management of educational institutions that are in conflict Nahd}atul Wat}an. To answer the key question is, non-Marxist-structuralist theory as a tool of analysis used in answering the above problems. Theory, among others, presented by Ralf Dahrendorf, who stated that the society united by a lack of freedom imposed. Certain position in society to delegate power and authority to another position, the difference in the distribution of authority becomes the determining factor of social conflict sistemati. Various positions in the community have the quality of different authorities. Authority does not lie inside the individual but in the position of this research uses a qualitative approach, data obtained from in-depth interviews (indepthinterview), observation and documentation, then interpreted, or translated to language researchers. These data to generate and describe the various conditions and situations none of the research object, and connecting these variables, and further description will be generated about the object of research, then the conclusions will be obtained. Our study argues that the organisiation has somewhat succeeded in moving toward the latter direction so much so that in the past 12 years or so it has built 820 schools according to Pancor group or 900 schools according to Anjani group across the provinse of Nusa Tenggara Barat.